The Effect of Spiritual Intelligence and Smartphone Use on Compassion of Students of Metta Maitreya Vocational School Pekanbaru in the 2024/2025 Academic Year - Sumarni Sumarni; Budi Utomo; Partono Partono (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
This study aims to determine the effect of spiritual intelligence and smartphone use on compassion of class X students at SMK Metta Maitreya Pekanbaru. The method used is quantitative with simple and multiple linear regression approaches. The instrument used was a questionnaire distributed to students and analyzed statistically to determine the relationship between variables. The results showed that there was a positive and significant influence between spiritual intelligence on student compassion with a correlation coefficient of 0.739 and an effective contribution of 52.17%. Meanwhile, the use of smartphones also has a positive and significant influence on compassion with a correlation coefficient of 0.290 and an effective contribution of 3.19%. The results of the multiple regression test show that spiritual intelligence and smartphone use simultaneously affect student compassion with a coefficient of determination of 55.36%. Thus, it can be concluded that spiritual intelligence has a more dominant influence on student compassion than smartphone use. This study recommends that schools focus more on developing students' spiritual intelligence as well as directing the use of smartphones in a direction that supports learning and character development.